MANAJEMEN LABA, KUALITAS LABA DAN KREDIBILITAS LAPORAN KEUANGAN - R. Rosiyana Dewi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2005)
The article shows about impact of earning management, especially in earning quality and credibility of financial report. Arrangement the article is based to literature and research prevously. Earning management is an terminology and topic which very important to understand in comprehension by the user of financial report.Financial report be conviced as a quantitative information which very useful in taking a decision. Many companies are very often to provide a financial report in well presentation to maximaize of prosperity and company market value, it is called earning management. In that case same treatments are able to applied as long as in right principles. Yet it can make a miss decision making and to result low quality of earnings.The high earning quality is earning which describe business prospect and realistic management treatment in considering reality business. A company earning report with a low quality same as incredible financial report.